2001
DOI: 10.1109/77.920242
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and relaxation of magnetic stress between magnet and superconductor in a levitation system

Abstract: The force of levitation experienced by a magnet on top of' a superconductor depends on position and how fast the magnet was put into that position. As a result, when the levitation force is measured as a function of the height of the magnet above the superconductor, a plot of the force versus height also depends on the rate at which the magnet position was changed during the experiment. We have measured this dependence of the levitation force (as a function of position) on the average rate of moving the magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…It has been accepted that the bulk superconductor is not in a really stable state after the drop; that is, the levitation force has a logarithmal decrease with time. [6][7][8] This phenomenon defined as levitation force relaxation has been investigated experimentally and theoretically. But most of their systems composed of the superconductor and magnet were coaxial 9 and there was no movement during the measurement.…”
mentioning
confidence: 99%
“…It has been accepted that the bulk superconductor is not in a really stable state after the drop; that is, the levitation force has a logarithmal decrease with time. [6][7][8] This phenomenon defined as levitation force relaxation has been investigated experimentally and theoretically. But most of their systems composed of the superconductor and magnet were coaxial 9 and there was no movement during the measurement.…”
mentioning
confidence: 99%
“…Because of the unsaturated magnetic field, the crossing originates from the magnetic hysteresis of the YBaCuO bulk superconductor with high critical current density. [19]. The maximum levitation force of Sample B at a speed of 20 mm/s is 5.7 N, which is the minimum value for all the measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is well known that the levitation force between a superconductor and a magnet is not only related to the electromagnetic properties of the superconductor, but also to the thickness and shape of the samples [14], initial cooling process [15,16], operating temperature [17], grain-orientation [18] etc. Postrekhin et al [19] reported the dependence of the levitation force on the average speed of moving the magnet (up to 12 mm/s) towards the superconductor and found that the maximum levitation force increased with increase in the moving speed of the magnet. In this work, we used an updated high temperature superconductor maglev measurement system [20] and measured the effects of the moving speed of the magnet (up to 20 mm/s) on the maximum levitation force of a melttextured superconductor.…”
Section: Introductionmentioning
confidence: 97%
“…[21][22][23][24][25] But there are few reports about the influence of waiting time on the levitation force in literature. In this work, we report a study of the influence of waiting time on the levitation force between a PM and FC and ZFC YBaCuO bulk superconductors.…”
Section: Introductionmentioning
confidence: 99%